IMPLEMENTASI PENDEKATAN INTEGRATED SYSTEM DALAM MENINGKATKAN MINAT DAN PRESTASI BELAJAR BAHASA ARAB SISWA KELAS XI DI MA NU MIFTAHUL ULUM MARGASARI-TEGAL - Akhmad Aufa Syukron (El-Tsaqafah : Jurnal Jurusan PBA, 2019)
This study aims to determine the concept of the IntegratedSystem approach, and the extent of the contribution of the IntegratedSystem Approach to learning interest and student learning achievementin learning Arabic.The approach used in the study is classroom actionresearch (PTK).Subjects in this study were students of class XI MA NUMiftahul Ulum Margasari.The results of this study indicate that in the preactioninterest of students was less interested as much as 40%, then afterthe implementation of the action in the first cycle increased to be quiteinterested as much as 53.30% (up 13.3%), in the second cycle increased to75% Interest (up by 21.7%), and in the third cycle experienced a degree ofinterest in the Interest category but the percentage increased to 78.30% (up3.3%). Based on Student Interest Questionnaire, from the average score ofpositive and negative criteria 33 items (25 positive items and 8 negativeitems) that have been obtained, the combined average score is (positivecriteria + negative criteria) = (22.82 + 2 , 79 = 25.61). 25.61 is a combinedaverage of positive and negative criteria, if it is reported to be 77.6%, theinterest in learning Arabic in class IX students is strong (interested) as muchas 77.6%. Based on the results of the tests, from the first, second and thirdcycles the value of Arabic subjects in class XI Science and Social Scienceswas above the KKM average, indicating that student learning achievementincreased by an average of 75.7 above the KKM score of 67.